Heterogeneity of Cardiovascular Effects of Second‐Line Glucose‐Lowering Therapies in Adults With Type 2 Diabetes Across the Range of Moderate Baseline Cardiovascular Risk - Yihong Deng; Eric C. Polley; Jeph Herrin; Kavya S. Swarna; David M. Kent; Joseph S. Ross; Bradley A. Maron; Mindy M. Mickelson; Rozalina G. McCoy (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) and sodium–glucose cotransporter‐2 inhibitors (SGLT2is) have favorable cardiovascular outcomes compared with dipeptidyl peptidase‐4 inhibitors (DPP4is) and sulfonylureas in adults with type 2 diabetes and high cardiovascular risk. How these benefits vary across lower levels of cardiovascular risk is unknown. Methods We used nationwide claims data to emulate a comparative effectiveness trial and examine the heterogeneity of treatment effects of GLP‐1RAs, SGLT2is, DPP4is, and sulfonylureas on major adverse cardiovascular events (MACEs) among adults with type 2 diabetes and moderate cardiovascular risk (annualized MACE risk 1%–5%, estimated using the annualized claims‐based MACE estimator). Results Among 386 276 included adults with type 2 diabetes, 25.2% had baseline ACME–predicted MACE risk >1% to ≤2% (lower‐risk patients) and 13.3% had ACME–predicted risk >4% to ≤5% (higher‐risk patients). By year 3 of treatment, higher‐risk patients derived greater absolute benefit than lower‐risk patients when treated with GLP‐1RAs versus sulfonylureas (absolute reduction in the estimated rate of MACE of 3.1% in higher‐risk patients and 1.6% in lower‐risk patients), SGLT2is versus sulfonylureas (absolute reduction, 3.9% in higher‐risk patients and 1.3% in lower‐risk patients), and GLP‐1RAs versus DPP4is (absolute reduction, 1.6% in higher‐risk patients and 0.5% in lower‐risk patients). The relative benefits for MACE were also greater in higher‐risk than lower‐risk patients with SGLT2is versus DPP4is (hazard ratio [HR], 0.78 [95% CI, 0.70–0.87] in higher‐risk patients; HR, 0.99 [95% CI, 0.88–1.12] in lower‐risk patients). Conversely, the relative benefits of DPP4is and GLP‐1RAs versus sulfonylureas were greater in lower‐risk patients: HR 0.76 (95% CI, 0.71–0.81) in lower‐risk and HR 0.91 (95% CI, 0.97–0.96) in higher‐risk patients for DPP4is versus sulfonylureas; HR 0.67 (95% CI, 0.58–0.78) in lower‐risk and HR 0.80 (95% CI, 0.70–0.93) in higher‐risk patients for GLP‐1RAs versus sulfonylurea. Benefits of SGLT2is and GLP‐1RAs were comparable across all risk levels. Conclusions Cardiovascular benefits of SGLT2is and GLP‐1RAs exist across all levels of moderate cardiovascular risk, reinforcing the importance of choosing glucose‐lowering therapies that can prevent MACE in all people with type 2 diabetes.